El consentimiento informado del paciente como limitante de la investigación científica en España - Sánchez Salazar, Diana Vanessa (2023)
The freedom of scientific research in Spain is ranked as a fundamental right, included in Title I of this country’s constitution. This freedom is highly protected and promoted every day by the Spanish government. However, the rights of the human beings involved in scientific experiments need to be clearly defined. The rise of biolaw as a new branch of law, establishing legal limits on me dical experimentation, has brought informed consent to the status of a fundamental right derived from human dignity and personal autonomy, a situation that has led to many debates among scholars of biolaw.